3D direct ink writing fabrication of high-performance all-solid-state micro-supercapacitors. (2nd July 2020) - Ovhal, Manoj Mayaji; Kumar, Neteesh; Kang, Jae-Wook
Abstract: We present the fabrication of flexible all-solid-state micro-supercapacitors (MSCs) by using 3D direct-ink-writing (DIW) technique. The conductive poly(3, 4-ethylenedioxythiophene)-poly(styrenesulfonate) (PEDOT:PSS) ink was printed by layer-by-layer fashion on flexible substrates. The MSC electrodes exhibit smooth surface and low sheet resistance. The flexible MSC fabricated by 3D DIW exhibits the areal capacitance per electrode of 31.6 mF cm −2, gravimetric capacitance of 15.6 F g −1, an energy density of 0.36 µWh cm −2, and power density of 80 µW cm −2 . The flexible MSC shows high cyclic and bending stability. We believed that the optimized 3D DIW fabrication has potential for roll-to-roll 3D printing flexible all-solid-state MSCs.